2020
DOI: 10.1016/s2213-2600(20)30053-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of blood eosinophils and exhaled nitric oxide in adults with mild asthma: a prespecified subgroup analysis of an open-label, parallel-group, randomised controlled trial

Abstract: Background: Whether blood eosinophil counts and exhaled nitric oxide (FeNO) are associated with important outcomes in mild asthma is unclear. Methods: This question was explored in a pre-specified analysis of a 52week, open-label, randomized, parallel-group trial in patients with mild asthma receiving only reliever inhalers, comparing salbutamol 200µg asneeded, maintenance budesonide 200µg twice-daily with salbutamol as needed, and budesonide/formoterol 200/6µg as-needed. Outcomes were compared between patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 30 publications
3
71
0
Order By: Relevance
“…As is often the case, the unexpected finding is a major one: namely, the exacerbation rate during longitudinal follow-up was not associated with circulating or sputum eosinophil counts. Blood eosinophils have repeatedly emerged as a risk factor for exacerbations in cross-sectional analyses ( 4 6 ), but although such associations have been confirmed in some ( 6 , 7 ) longitudinal studies on this topic, they have not been confirmed in all such longitudinal studies ( 8 ), and this includes the present one ( 3 ). This may be linked to differences in asthma severity, phenotype, and treatment, but it certainly suggests that prospective assessment provides its own information in search for asthma biomarkers.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…As is often the case, the unexpected finding is a major one: namely, the exacerbation rate during longitudinal follow-up was not associated with circulating or sputum eosinophil counts. Blood eosinophils have repeatedly emerged as a risk factor for exacerbations in cross-sectional analyses ( 4 6 ), but although such associations have been confirmed in some ( 6 , 7 ) longitudinal studies on this topic, they have not been confirmed in all such longitudinal studies ( 8 ), and this includes the present one ( 3 ). This may be linked to differences in asthma severity, phenotype, and treatment, but it certainly suggests that prospective assessment provides its own information in search for asthma biomarkers.…”
mentioning
confidence: 75%
“…This strongly indicates that fluctuation analysis of biomarker time series, rather than linear, single-time-point assessments, is required to identify biomarkers of exacerbation-prone asthma. In fact, the prospective follow-up studies by SARP-3 ( 3 , 14 ), Novel START (Novel Symbicort Turbuhaler Asthma Reliever Therapy) ( 6 ), Hi-CARAT (Hokkaido-based Investigative Cohort Analysis for Refractory Asthma) ( 8 ), ADEPT (Airways Disease Endotyping for Personalized Therapeutics) ( 14 ) and U-BIOPRED (Unbiased Biomarkers for the Prediction of Respiratory Disease Outcome) ( 14 ) will be highly suited to test and collectively validate whether the temporal behavior of composite biomarkers provides a complementary phenotypic signal that is relevant for identification of frequent exacerbators.…”
mentioning
confidence: 99%
“…In addition, previous studies have demonstrated that high B-Eos counts are related to poor asthma control, risk of exacerbations, and response to maintenance of inhaled corticosteroids. [36][37][38] It is becoming crucial that the measurement of blood eosinophils adds predictive and prognostic information to airway disease. [39] Although FeNO and B-Eos are part of the Th2 in ammation cascade, these two biomarkers are regulated by different in ammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The use of this technique in the clinic established that the pattern of airway dysfunction, the severity of impaired function, demographic characteristics (including diagnostic label), and severity of symptoms or lung function impairment provide a very limited insight into the nature and severity of lower airway inflammation ( 4 6 ). It also become clear that identification of type 2–high eosinophilic airway inflammation is important because it is associated with an increased risk of exacerbations of asthma ( 7 9 ) and chronic obstructive pulmonary disease (COPD) ( 10 ) and a better response to corticosteroids ( 9 11 ) and biologic agents targeting type 2 cytokines ( 12 16 ). Thus, an approach to risk stratification and the introduction and titration of treatment that relies on symptoms and recognition of different patterns of airflow limitation is flawed.…”
mentioning
confidence: 99%
“…Second, biomarker-directed risk stratification and reduction should be extended beyond COPD and severe asthma clinics. There is now evidence from large intervention studies in mild, moderate, and severe asthma that the blood eosinophil count is independently associated with up to a fivefold increased risk for severe exacerbations as well as a greater response to ICS and biological agents ( 8 , 9 , 14 , 26 ). Most studies have shown that another easy to measure biomarker, exhaled nitric oxide, adds prognostic and predictive information to blood eosinophil–based stratification ( 8 , 26 ).…”
mentioning
confidence: 99%